The microbiome of alpine snow algae shows a specific inter-kingdom connectivity and algae-bacteria interactions with supportive capacities - Krug, Lisa (ISME J, 2020)
Mutualistic interactions within microbial assemblages provide a survival strategy under extreme conditions; however, little is known about the complexity of interaction networks in multipartite, free-living communities. In the present study, the interplay within algae-dominated microbial communities exposed to harsh environmental influences in the Austrian Alps was assessed in order to reveal the interconnectivity of eukaryotic and prokaryotic inhabitants. All analyzed snowfields harbored distinct microbial communities. Network analyses revealed that mutual exclusion prevailed among microalgae in the alpine environment, while bacteria were mainly positively embedded in the interaction networks. Especially members of Proteobacteria, with a high prevalence of Oxalobacteraceae, Pseudomonadaceae, and Sphingomonadaceae showed genus-specific co-occurrences with distinct microalgae. Co-cultivation experiments with algal and bacterial isolates confirmed beneficial interactions that were predicted based on the bioinformatic analyses; they resulted in up to 2.6-fold more biomass for the industrially relevant microalga Chlorella vulgaris, and up to 4.6-fold increase in biomass for the cryophilic Chloromonas typhlos. Our findings support the initial hypothesis that microbial communities exposed to adverse environmental conditions in alpine systems harbor inter-kingdom supportive capacities. The insights into mutualistic inter-kingdom interactions and the ecology of microalgae within complex microbial communities provide explanations for the prevalence and resilience of such assemblages in alpine environments.